Norbert Elias at the University of Leicester - Korte, Hermann (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The main aim of the paper is to investigate the role and contribution played by Norbert Elias in the early years of the new settled sociology department of Leicester. Starting from the file on Elias kept by the University of Leicester itself - a file that contains Elias’ application, various testimonials, carbon copies of the letters of the Academic Registrar, as well as originals of Elias’s letters - the Author aims to enlarge the renowned information about academic career and everyday life of Elias in the English period, adding a new angle, “the bureaucratic one”, on this period of his life.